ADVANCEMENT IN DIAGNOSTIC AND SURGICAL MANAGEMENT OF ECHINOCOCCOSIS IN PEDIATRIC PATIENTS - Sharapov Ilxamberdi Kamalovich (Web of Journals Publishing, 2025)
This study evaluates improved diagnostic and surgical strategies for pediatric echinococcosis, demonstrating the effectiveness of combined imaging and serology, and the benefits of minimally invasive techniques. Findings support stage-specific surgical algorithms that enhance safety, reduce complications, and provide practical guidance for optimizing outcomes in children with this parasitic disease.
Keywords: Echinococcosis, pediatric parasitic disease, hydatid cyst, ultrasonographic diagnosis, computed tomography imaging, serological diagnostics, enzyme-linked immunosorbent assay, laparoscopic surgery, minimally invasive techniques, surgical spillage prevention.